2023
DOI: 10.3389/fonc.2022.1094400
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of tumor-associated macrophages detected by immunostaining in diffuse large B cell lymphoma: A meta-analysis

Abstract: BackgroundThe prognostic implication of tumor-associated macrophages (TAMs) in the microenvironment of diffuse large B cell lymphoma (DLBCL) remains controversial.MethodsA systematic and comprehensive search of relevant studies was performed in PubMed, Embase and Web of Science databases. The quality of the included studies was estimated using Newcastle-Ottawa Scale (NOS).ResultsTwenty-three studies containing a total of 2992 DLBCL patients were involved in this study. They were all high-quality studies scorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In most studies, high CD163 expression was correlated with an inferior prognosis. Controversial findings, as well as significant heterogeneity, have been reported regarding the contribution of CD163 expression in non-Hodgkin’s lymphoma disease activity, specifically in DLBCL, mantle cell lymphoma, follicular lymphoma, and T lymphoma [ 44 , 45 ]. The majority of studies have compared CD163 and CD68 immunohistochemical staining intensity in tissue biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, high CD163 expression was correlated with an inferior prognosis. Controversial findings, as well as significant heterogeneity, have been reported regarding the contribution of CD163 expression in non-Hodgkin’s lymphoma disease activity, specifically in DLBCL, mantle cell lymphoma, follicular lymphoma, and T lymphoma [ 44 , 45 ]. The majority of studies have compared CD163 and CD68 immunohistochemical staining intensity in tissue biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…S100A8 could induce a pro-inflammatory response, including inflammatory cytokines and chemokines, and introduce the tumor-promoting effect and suppression of anti-tumor immune responses ( 14 , 19 ). Tumor-associated macrophages (TAMs) can have a spectrum of phenotypes and be associated with a poor prognosis ( 71 ), A meta-analysis demonstrated that the high abundance of M2 TAMs in TME might be related to an adverse clinical outcome for DLBCL patients ( 72 ). The interaction with S100A8 can influence several aspects of tumor biology, which is associated with immunosuppression and TME remodeling through driving the polarization of macrophages toward an M2-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated TAMs in the tumorigenesis and invasive progression of DLBCL [ 22 24 ]. Meta-analyses revealed that high-density M2 TAMs within the tumor microenvironment are indicative of poorer OS in DLBCL [ 85 ]. Furthermore, Ma RY et al identified IFN_TAMs through scRNA-seq, characterized by heightened glycolytic activity, while its role in DLBCL remains unexplored.…”
Section: Discussionmentioning
confidence: 99%